Type A Aortic Dissection in a Previously Healthy Pregnant Patient: A Challenging Dilemma, Case Report, and Literature Review - Elham Bateni; Maryam Dehghan; Zeinab Ahmadikia (Case Reports in Cardiology)
Aortic dissection (AoD) is a rare fatal condition in which tearing in the intima causes a false channel in the aorta and can lead to rupture. AoD is classified as the DeBakey classification (Types I, II, III) and Stanford classification (Types A and B). Women with underlying risk factors such as hypertension, smoking, bicuspid aortic valve, and connective tissue disorders are at risk for pregnancy-related AoD. These risk factors may not be recognized until the AoD occurs during pregnancy. We describe an acute incidence of type A AoD in the second trimester of pregnancy. A multiparous woman with no previously known risk factor presented with nonspecific chest pain. She was found to have AoD and underwent successful surgical intervention. This case demonstrates the importance of vigilance in the evaluation of pregnant women with new cardiopulmonary symptoms. A multidisciplinary approach can save the mother and the fetus.